2017
DOI: 10.1093/femsyr/fox032
|View full text |Cite
|
Sign up to set email alerts
|

Increasing the intracellular isoprenoid pool in Saccharomyces cerevisiae by structural fine-tuning of a bifunctional farnesyl diphosphate synthase

Abstract: Farnesyl diphosphate synthase (FPPS) is a key enzyme responsible for the supply of isoprenoid precursors for several essential metabolites, including sterols, dolichols and ubiquinone. In Saccharomyces cerevisiae, FPPS catalyzes the sequential condensation of two molecules of isopentenyl diphosphate (IPP) with dimethylallyl diphosphate (DMAPP), producing geranyl diphosphate (GPP) and farnesyl diphosphate (FPP). Critical amino acid residues that determine product chain length were determined by a comparative st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 44 publications
0
10
1
Order By: Relevance
“…The strain ERS103 with Erg20 F96W performed better than others and generated 575.6 mg/L α-santalene. It has been reported that the mutation Erg20 A99G favors considerably the accumulation of FPP; however, the α-santalene titer of the strain containing Erg20 A99G (75.3 mg/L) was lower than that of stain containing Erg20 in our study . To explore the FPP synthase catalyzed into the Z-configuration FPP, which is not essential for cell growth, we observed that, in the strains containing Rv1086 and zFPS, only a trace amount of α-santalene was detected, as the ClSS used in this study preferred 2E,6E-FPP as a substrate.…”
Section: Resultscontrasting
confidence: 54%
See 1 more Smart Citation
“…The strain ERS103 with Erg20 F96W performed better than others and generated 575.6 mg/L α-santalene. It has been reported that the mutation Erg20 A99G favors considerably the accumulation of FPP; however, the α-santalene titer of the strain containing Erg20 A99G (75.3 mg/L) was lower than that of stain containing Erg20 in our study . To explore the FPP synthase catalyzed into the Z-configuration FPP, which is not essential for cell growth, we observed that, in the strains containing Rv1086 and zFPS, only a trace amount of α-santalene was detected, as the ClSS used in this study preferred 2E,6E-FPP as a substrate.…”
Section: Resultscontrasting
confidence: 54%
“…It has been reported that the mutation Erg20 A99G favors considerably the accumulation of FPP; however, the α-santalene titer of the strain containing Erg20 A99G (75.3 mg/L) was lower than that of stain containing Erg20 in our study. 24 To explore the FPP synthase catalyzed into the Z-configuration FPP, which is not essential for cell growth, we observed that, in the strains containing Rv1086 and zFPS, only a trace amount of α-santalene was detected, as the ClSS used in this study preferred 2E,6E-FPP as a substrate. Seeking terpene synthases that prefer 2Z,6E-FPP or 2Z,6Z-FPP as substrates and the construction of an orthogonal pathway to the strain growth can also be a research direction to reduce the impact caused by FPP diversion in the future.…”
Section: Resultsmentioning
confidence: 77%
“…Therefore, the initial strategy for engineering higher 1,8-cineole titers focused on optimizing and balancing expression levels of the two terminal enzymes: GPPS and 1,8-cineole synthase. Engineering a high monoterpene titer requires a balance between GPPS and terpene synthase activities that provides sufficient flux to accumulate the target product while avoiding growth-inhibitory levels of GPP [ 11 , 27 ]. Promoters for these synthases were selected from native R. toruloides genes.…”
Section: Resultsmentioning
confidence: 99%
“…Engineering a high monoterpene titer requires a balance between GPPS and terpene synthase activities that provides su cient ux to accumulate the target product while avoiding growth-inhibitory levels of GPP [11,27]. Promoters for these synthases were selected from native R. toruloides genes.…”
Section: Transcriptomics and Proteomics Analysis Of α-Bisabolene Prodmentioning
confidence: 99%